Huntsman spiders (Araneae: Sparassidae) from Xishuangbanna Rainforest, China - Liu, Jie; Li, Shuqiang; Jäger, Peter (Zootaxa, 2010)
An extensive faunal survey of spiders from Xishuangbanna was carried out over one year (July 2006–August 2007) using various collecting techniques (ground pitfall traps, trunk pitfall traps, fogging and hand collecting). Three known Sparassidae species were collected: Heteropoda tetrica Thorell, 1897, Pseudopoda songi Jäger, 2008, and Pseudopoda namkhan Jäger, Pathoumthong & Vedel, 2006, the latter reported for the first time from China. Thelcticopis zhengi sp. nov. is described and illustrated based on males and females. All specimens are deposited in the Institute of Zoology, Chinese Academy of Sciences in Beijing (IZCAS) and Research Institute Senckenberg in Frankfurt am Main (SMF).